Utility Regulation and Risk Allocation: The Roles of Marginal Cost Pricing and Futures Markets. - Cowan, S (2004)
The effects on consumer welfare of requiring a utility facing cost or demand risk to use either a fixed retail price or marginal cost pricing are assessed. With marginal cost pricing and cost volatility an efficient futures market allows consumer welfare to be at least as high in every state as with the fixed price. With demand risk marginal cost pricing can benefit the consumer in every state without harming the firm if the profit difference is transferred to the consumer. A futures market can act as a partial replacement for the transfer.